Supervisi Kurikulum Darurat pandemi Covid 19 Pada Pembelajaran Pendidikan Agama Islam - Zuhri, Mohammad; Dini, Sri Susanti Tjahja (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The impact of the Covid-19 pandemic on the world of education lies in the learning process, although students cannot carry out face-to-face learning activities such as usually, but teaching and learning activities should not be stopped because at the age of Child or adolescent age is the ideal age to seek knowledge, especially science Religion, then to maintain the quality of student learning and even better then the need for guidance and supervision from the education supervisor or the usual This is called educational supervision. The research method used in this research is qualitative approach with the type of case study. The data collection technique uses interview, observation, and documentation techniques. After the data is collected, the process is carried out data coding and checking the validity of the data using a credibility test and confirmability. The result is that the supervisor formulates ideas for help teachers complete their tasks, improve teacher professionalism in the form of encouragement, guidance, and opportunities for the growth of skills and abilities of teachers, then carry out the stages of planning, implementing, evaluating, following up, and reporting